Catholics, conflicts and choices : an exploration of power relations in the Catholic Church - Coco, Angela; Cambridge eBooks (Durham : Acumen Publishing, 2013)
Many Catholics today are disenchanted with the Church's continuing distrust of women and laity. But, despite this widespread dissatisfaction, traditional power relations have hardly changed over the last century. Catholics, Conflicts and Choices presents detailed interviews with lay people, priests, Sisters, and Christian Brothers, each discussing their personal struggles with church teachings and practices. The conversations are selected to illustrate different experiences of power relations - particularly different aspects of gender dynamics - within the organisational structures of the Church. The interviews are examined within a framework of feminist, sociological and psychological theory. Catholics, Conflicts and Choices reveals how, despite a long history of challenging official notions of authority and obedience and assumptions about intimate relationships, there is little potential for change if the established power relations of the Church are not confronted.
When this story began -- Growing up Catholic -- Thinking about experience -- Sharing knowledge -- Questioning the Catholic institution -- Managing one's self -- Catholic housework -- A most (un)natural order.
Title from publisher's bibliographic system (viewed on 02 Oct 2015).
Keywords: Women in the Catholic Church; Laity -- Catholic Church; Authority -- Religious aspects -- Catholic Church; Electronic books